Perbandingan Kasus Nekrosis Pulpa dengan Gangren Radiks di Poli Gigi UPTD Puskesmas Baturiti II Tabanan - Kadek Adisty Maharani Putri; Ni Putu Idaryati; Ni Luh Putu Ariani (Pusat riset dan Inovasi Nasional, 2025)
Dental and oral health is still a significant problem in Indonesia. Riskesdas 2018 data shows that 57.6% of the population has dental and oral problems, while only 2.8% brush their teeth properly. This condition is a serious concern because untreated dental caries can develop into pulp necrosis and subsequently radical gangrene. Both conditions have the potential to cause infections that can interfere with people's quality of life if not treated immediately. This study aims to compare the prevalence of visits to pulp necrosis and radical gangrene based on gender and age at the UPTD Baturiti II Tabanan Health Center during January-March 2025. The research uses a quantitative descriptive method with a purposive sampling technique based on secondary data from the E-Puskesmas system. The results showed that the prevalence of gangrene radicals (7.2%) was higher than that of pulp necrosis (5.9%). Female patient visits were more dominant in both cases, namely 52.7% in pulp necrosis and 56.5% in radical gangrene. The age distribution showed that the age group of 20–44 years dominated in cases of pulp necrosis (42.1%), while gangrene radicals occurred more in the age group of 45–59 years (34.8%). These results indicate a delay in dental care that contributes to the progression of the disease. The high number of these incidents cannot be separated from behavioral factors and the low level of public knowledge in maintaining dental and oral health. Therefore, increasing communication, information, and education efforts at the level of primary health care facilities is essential to encourage public awareness. Early detection and timely treatment are key in preventing serious complications such as pulp necrosis and radical gangrene.